2019
DOI: 10.1016/j.jacl.2018.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Increased usual physical activity is associated with a blunting of the triglyceride response to a high-fat meal

Abstract: Background: Post-prandial lipemia (PPL), defined as a prolonged or elevated rise in triglycerides that accompanies fat feeding, is a significant risk factor for coronary heart disease (CHD) and associated comorbidities. The impact of PPL on CHD risk is underscored by the preponderance of each day spent in the post-prandial state. Objective: In this study, we evaluated cross-sectionally the association between usual (i.e., non-interventional) physical activity and the 6-hour triglyceride response to a standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…This study determined the fasting lipid profiles of regular kratom users as compared to healthy subjects that do not use kratom. It evaluated the associations between kratom use characteristics and serum triglyceride, total cholesterol, LDL, and HDL levels, accounting for confounding factors, such as age, employment status, cigarette smoking, physical activity, and BMI among the kratom users [24][25][26][27]. We found that the serum total cholesterol and serum LDL levels were significantly lower in kratom users compared to healthy subjects who did not use…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This study determined the fasting lipid profiles of regular kratom users as compared to healthy subjects that do not use kratom. It evaluated the associations between kratom use characteristics and serum triglyceride, total cholesterol, LDL, and HDL levels, accounting for confounding factors, such as age, employment status, cigarette smoking, physical activity, and BMI among the kratom users [24][25][26][27]. We found that the serum total cholesterol and serum LDL levels were significantly lower in kratom users compared to healthy subjects who did not use…”
Section: Discussionmentioning
confidence: 93%
“…To achieve the second objective of the study, the individual associations between kratom use characteristics, such as the age of first kratom intake; duration of kratom use; average daily frequency of kratom use and average daily kratom consumption (independent variables); and serum triglyceride, serum total cholesterol, serum LDL, and serum HDL levels among kratom users (dependent variable), were assessed using simple linear regression analysis. We took into consideration possible confounding factors that may influence lipid profile, such as age, employment status, cigarette smoking, BMI, and physical activity [24][25][26][27]. Variables with p < 0.1 were entered into the multiple linear regression models as independent variables, and serum triglyceride, serum total cholesterol, serum LDL, and serum HDL levels were entered as dependent variables.…”
Section: Discussionmentioning
confidence: 99%
“…First, the Amish tend to be far more physically active than their non-Amish counterparts, as we 14 and others 15 16 have previously documented. The protective effects of physical activity on cardiometabolic health are well documented, including in the Amish, 17 and the more active Amish lifestyle may contribute to less diabetes, hypertension, and high cholesterol in this population. Second, the structure of Amish culture is very different from the non-Amish, and some aspects of this culture may confer additional benefits to cardiometabolic health.…”
Section: Discussionmentioning
confidence: 98%
“…In particular, obesity has a robust relationship with depressive symptoms (Blasco et al, 2020) and TG levels (Skinner et al, 2015). Proper dietary habits, such as a lower-carbohydrate diet (Thom & Lean, 2017) and physical activity, may subsequently reduce TG (Mitchell et al, 2019) (Cameron et al, 2004;Lian et al, 2019;Moore et al, 2017;NCEP, 2002;Pratt & Brody, 2014;Pucci et al, 2017;Son & Kim, 2019). In general, the prevalence of MetS differs by age and gender, and in advanced age, this prevalence increases much more sharply in women than in men (Pucci et al, 2017).…”
Section: Discussionmentioning
confidence: 99%